The MaTE Tool-Enabling Engaged Scholars at a Regional University - Patrick A. Crookes; Fabienne C. Else; Kylie M. Smith (The University of Alabama, 2022)
Providing institutionally recognized evidence of community engaged scholarship has long been problematic for engaged scholars when applying for recognition through promotion or probation pathways. To combat this, the University of Wollongong [in New South Wales, Australia] developed an online tool for use by engaged scholars to track and measure their engagement activities in a consistent and institutionally recognized form. This article outlines the process that was undertaken to develop the online system for measuring and tracking engagement (the MaTE tool). It outlines the initial recognition of the key issues arising from a comprehensive review of the literature; the drafting process undertaken to develop a prototype for the tool; and the interview stage and subsequent re-drafting process and finalization of the tool. The article concludes with a consideration of future directions for the tool and its further implementation at the university.